Penggunaan Tanah Aset Milik PT. Kereta Api oleh Masyarakat - Ramdlon Mahuraden Tuakia; Ana Silviana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
One of the main problems until now has not received clear regulations, namely land issues, and the number of conflicts that arise within the community, as well as in the use of land by utilizing and using PT assets. Indonesian Railways (PT. KAI) which is currently in the use and development of businesses to support railway activities, but where there is a lot of use and control of land assets by the community physically. So in the juridical sense of assets owned by PT Kreta Api Indonesia, it can be said that there is uncertainty in the law of land rights, so in this case, an appropriate policy is needed in achieving clarity in the use of land which is as follows the applicable land law regulations. So in writing this study to find out the legal certainty and validity of the use of PT Kreta Api Indonesia's land assets by the community outside the railway activities provided by PT Kreta Api Indonesia. This research uses legal research methods through the use of empirical juridical research methods, with details of writing descriptive analysis. The technique for this research looks at the juridical aspects of the form of land utilization of PT. KAI by the community with a Lease Agreement and the granting of IMB on HPL or HGB. The legal basis for granting rights in the use of land assets of PT. KAI is outside of the activities, businesses, and supports of PT. Kai. The use and utilization of PT KAI's assets by the community are regulated in Spatial Planning in the local area based on Law No. 24 of 1992 and Presidential Decree No. 16 of 1994. Land utilization outside the activities of PT. KAI is contrary to Article 44 of the Agrarian Principles Law, so in this legal act, it can be said to be null and void.